Effect of period of sugarcane cultivation on the abundance and distribution of weed seeds in the soil profile - Adereti,R.O. (2014)
An experiment was laid down in a screen house to determine the distribution of weed seeds at different soil depths and periods of cultivation of sugarcane in Ilorin, Nigeria. Soil samples from different depth levels (0-10 cm, 11-20 cm and 21-30 cm) were collected after harvesting of canes from three different land use fields (continuous sugarcane cultivation for > 20 years, continuous sugarcane cultivation for < 10 years after long fallow period and continuous sugarcane cultivation for < 5 years after long fallow period) in November, 2012. One kilogram of the sieved composite soil samples was arranged in the screen house and watered at alternate days. Germinating weed seedlings were identified, counted and then pulled out for the period of 8 months. Land use and soil depth had a highly significant (p £ 0.05) effect on the total number of weeds that emerged from the soil samples. The 010 cm of the soil depth had the highest weed seedlings that emerged. There was an equal weed seed distribution at the 11-20 cm and 21-30 cm depths of the soil. Sugarcane fields which have been continuously cultivated for a long period of time with highly disturbing soil tillage practices tend to have larger seed banks in deeper soil layers (11-20 cm and 21-30 cm) while recently opened fields had significantly larger seed banks at the 0-10 cm soil sampling depth.